Correlation between pain sensitivity and postoperative sleep disturbance in adult patients undergoing intestinal polypectomy under general anaesthesia: a prospective cohort study - Yan Li; Qian Liu; Yun Chen; Ziyan Pan; Haichuan He; Jiangwen Yin (BMJ Open)
Objectives Postoperative sleep disturbance (PSD), a common clinical complication, can be influenced by various factors. This article aims to investigate the association between pain sensitivity and PSD in adult patients (<65 years old) undergoing elective intestinal polypectomy under general anaesthesia.Design Nationwide register-based cohort study.Setting The First Affiliated Hospital of Shihezi University, Shihezi, 832003, ChinaParticipants A total of 246 patients undergoing elective intestinal polypectomy under general anaesthesia were selected from December 2023 to September 2024 (aged 18-64 years, about 59% men).Primary and secondary outcome measures Athens Insomnia Scale (AIS) scores and sleep parameters, including sleep stages, efficiency, awakening times and sleep latency, were recorded one day before and after surgery.Methods A total of 246 adult patients (<65 years old) undergoing elective intestinal polypectomy under general anaesthesia were selected from December 2023 to September 2024. Preoperative pain sensitivity was assessed using quantitative sensory testing. The AIS was employed to evaluate the sleep quality of the patients before and after the operation. Additionally, a sleep monitor was used to record various sleep indicators of the patients on the night before and the first night after the operation, including sleep stages, efficiency, awakening times and sleep latency. Multivariate logistic regression analysis was performed to analyse the relationship between pain sensitivity and PSD.Results Among the included patients who underwent elective intestinal polypectomy under general anaesthesia, 54 individuals (21.95%) developed PSD. Patients with high pain sensitivity had an increased risk of developing PSD (adjusted OR=2.789, 95% CI=1.020 to 7.628, p=0.046). In this study, logistic regression analysis using SPSS software identified three independent risk factors associated with PSD: pain sensitivity, presurgery sleep latency and the number of awakenings on the night before surgery. Receiver operating characteristic (ROC) curve analysis demonstrated that the areas under the curve for pain sensitivity grouping, sleep latency on the night before surgery and the number of awakenings on the night before surgery were 0.678, 0.656 and 0.645, respectively. According to ROC curve analysis, the areas under the curves of pain sensitivity, presurgery sleep latency and the number of awakenings on the night before surgery for PSD were all >0.5, but the diagnostic value of each factor alone was still low. The calibration curve for the combined model showed an area under the curve of 0.776, which was higher than the individual diagnostic factors.Conclusions In adult patients (<65 years old) undergoing elective intestinal polypectomy under general anaesthesia, the difference in pain sensitivity is associated with the occurrence of PSD, and patients with high pain sensitivity are prone to experiencing PSD.